2015
DOI: 10.1103/physreva.91.033811
|View full text |Cite
|
Sign up to set email alerts
|

Parity-time-antisymmetric atomic lattices without gain

Abstract: Lossy atomic photonic crystals can be suitably tailored so that the real and imaginary parts of the susceptibility are, respectively, an odd and an even function of position. Such a parity-time (P T ) space antisymmetry in the susceptibility requires neither optical gain nor negative refraction, but is rather attained by a combined control of the spatial modulation of both the atomic density and their dynamic level shift. These passive photonic crystals made of dressed atoms are characterized by a tunable unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…In particular, for φ d = ±π/4 and p = 0, δ ds (z) turns out to be a sine function of z, i.e., in quadrature with the atomic density distribution N j (z) along the optical lattice. In this case, the correlated modulations in N j (z) and δ ds (z) result in a P T -antisymmetric susceptibility with its real (imaginary) part being an odd (even) function of the position z [2,43]. This implies, in particular, both that the system is a pseudo-Hermitian one [46] and that it satisfies the spatial Kramers-Kronig relations [3].…”
Section: A the Photonic Crystalmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, for φ d = ±π/4 and p = 0, δ ds (z) turns out to be a sine function of z, i.e., in quadrature with the atomic density distribution N j (z) along the optical lattice. In this case, the correlated modulations in N j (z) and δ ds (z) result in a P T -antisymmetric susceptibility with its real (imaginary) part being an odd (even) function of the position z [2,43]. This implies, in particular, both that the system is a pseudo-Hermitian one [46] and that it satisfies the spatial Kramers-Kronig relations [3].…”
Section: A the Photonic Crystalmentioning
confidence: 99%
“…Such atoms are driven into the four-level N configuration by three coherent fields of frequencies (real amplitudes) ω p (E p ), ω c (E c ), and ω d (E d ) [2,43] [see Fig. 1 …”
Section: A the Photonic Crystalmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showed that light propagation in optical lattices of driven cold atoms with PT-antisymmetric susceptibilities, i.e. χ(z) = −χ * (−z), exhibited EPs (also known as non-Hermitian degeneracies), at which complete unidirectional reflectionless light propagation was observed [91,92].…”
Section: Unidirectional Reflectionless Propagation In Pt-symmetric Symentioning
confidence: 99%